Re-evaluating the Alignment of Omnivorous Choice and Animal Farming with Sustainable Development: Insights from Care Ethics - Mukherjee, Upamita; Venkataraman, Prabhu (Problemy Ekorozwoju, 2024)
<!--StartFragment--> C Care ethics plays a significant role in the philosophical investigation of sustainable development. This paper is an attempt to comprehend the intricate relationship between care ethics and omnivorism, particularly in the context of economic sustainability, animal farming, and holistic well-being. Care ethics emphasizes empathy, relationships, and responsibility, basically applied to human interactions with other humans, animals, and the environment. Omnivorism denotes the consumption of both animal-based foods and plants. Inspecting all these concepts through the lens of economic sustainability involves considering the impact of consumption choices on agriculture, resources, and environmental costs. Self-care sustainability involves assessing personal choices regarding health, well-being, and the broader ecological system. By examining omnivorism and care ethics in the context of these two sustainability dimensions, this paper finally proposes to provide insights into the complex interplay between moral values, consumption habits, and the long-term well-being of individuals and the planet. <!--EndFragment-->